Discovering the Depths of Scientific Literacy: Evaluating XI-Grade Student Progress Using Bybee's Definition - Permatasari, Putri; Fitriza, Zonalia (Universitas Negeri Padang, 2025)
This study evaluates the scientific literacy of XI-grade students in understanding science and technology concepts amid rapid technological advances. Scientific literacy is the ability to apply learned concepts to real-world phenomena. A cluster random sampling of 30 students was assessed using a reasoned multiple-choice test. Results showed very inadequate scientific literacy, with an average accuracy of 33.167%. Further analysis classified 34.3% as illiterate, 65.1% as nominally literate, 0.23% as functionally literate, and 0.33% as conceptually literate. These findings highlight the need for improved teaching strategies that emphasize contextual learning and real-world applications to enhance students' scientific literacy.